2013
DOI: 10.4236/fns.2013.43036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Moringa oleifera</i> Leaf Powder Supplementation on Some Quality Characteristics of Wheat Bread

Abstract: The effect of Moringa oleifera leaf powder supplementation on some physico-chemical and sensory properties of wheat bread was determined. Bread was prepared from varying proportions of 100%, 99%, 98%, 97%, 96% and 95% wheat flour supplemented with 0%, 1%, 2%, 3%, 4% and 5% Moringa oleifera leaf powder respectively. The bread samples were allowed to cool at ambient temperature (30˚C ± 1˚C) and analysed for some physical properties, proximate composition, and sensory attributes. Moringa leaf powder addition sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
60
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 9 publications
(11 reference statements)
23
60
1
1
Order By: Relevance
“…1 indicated no difference between sample containing 2.5% of MLP (2.48 cm 3 /g) and control bread (2.50 cm 3 /g); a significant decrease of specific volume was observed when higher amount of MLP was added. These results are consistent with those previously published for wheat bread enriched with MLP [4,9].…”
Section: Physical Properties Of Gluten-free Breads Fortified With Mlpsupporting
confidence: 83%
See 3 more Smart Citations
“…1 indicated no difference between sample containing 2.5% of MLP (2.48 cm 3 /g) and control bread (2.50 cm 3 /g); a significant decrease of specific volume was observed when higher amount of MLP was added. These results are consistent with those previously published for wheat bread enriched with MLP [4,9].…”
Section: Physical Properties Of Gluten-free Breads Fortified With Mlpsupporting
confidence: 83%
“…(2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid), DPPH (2,2-diphenyl-1-picrylhydrazyl), Folin-Ciocalteau reagent, ammonium thiocyanate, Fe SO 4 , and sodium thiocyanate were purchased from SigmaAldrich company (Poznan, Poland). All others chemicals were of analytical grade.…”
Section: Abtsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be due to the characteristic bitter taste imparted by the higher quantity of Moringa leaf powder [7]. A similar trend was observed by Sengev et al [21] with Moringa oleifera leaf powder substituted wheat bread. Fuglie [7] reported that, though there is no known side effect as to over consumption of Moringa, it has a characteristics bitter taste when consumed directly or added in higher concentration to food.…”
Section: Protein Qualitysupporting
confidence: 67%